DEGRADASI LIGNIN DARI AMPAS SAGU MENGGUNAKAN FOTOKATALIS TiO2 DAN UJI AKTIFITAS ANTIBAKTERI - Irwan Irwan; Wayuningsih Wayuningsih; Muhammad Natsir (CV. ADIBA AISHA AMIRA, 2023)
This study reports the effectiveness of the TiO2 photocatalyst in degrading lignin in sago pulp waste and testing its antibacterial activity on Escherichia coli. The lignin degradation process was carried out using a TiO2 photocatalyst in a photocatalytic reactor operated with a UV lamp. The degradation results of sago pulp waste were analyzed using a UV-Vis spectrophotometer to measure the decrease in absorbance. The results showed that the TiO2 photocatalyst was able to degrade lignin from sago pulp waste with high effectiveness. It is proved that the concentration of lignin decreased with increasing photooxidation time. In addition, the results of the degradation of sago pulp waste also showed antibacterial activity against E. coli, as seen from the presence of very strong inhibition zones at concentrations of 500 ppm and 1000 pmm with a photooxidation time of 250 minutes. This indicates that the potential use of degradation products as antimicrobial compounds.